Public Service Innovation Through E-Government: A Case Study of the Bandung District Court, Class 1a Special - SHABIRA, Azka Lina Sani; TINDAON, Susi Susanti; SUDRAJAT, Achmad Sodik; HARAHAP, Anggi Syahadat (Journal of Governance, Taxation and Auditing, 2025)
Digital transformation in the judicial sector represents a key aspect of e-Government implementation, aimed at enhancing the effectiveness, transparency, and accountability of public services. The Supreme Court of the Republic of Indonesia has developed various technology-based innovations, including the Case Tracking Information System (SIPP), e-Court, Integrated Service Center (PTSP) Online, and the Supervisory Information System (SIWAS). The Bandung District Court Class 1A Special, as one of the courts with a high caseload, faces an urgent need to adopt digital service innovations. This study aims to analyze the implementation of e-Government-based public service innovations in the Bandung District Court Class 1A Special. A qualitative approach with descriptive analysis was employed, supported by secondary data from regulations, official Supreme Court reports, and SIPP records of the Bandung District Court. The analysis was carried out using the SWOT-TOWS framework to identify enabling factors, barriers, and opportunities for system development. The findings indicate that e-Government innovations have improved service accessibility, accelerated administrative processes, and strengthened case transparency. However, challenges remain, including limited platform integration, non-real-time data updates, uneven human resource capacity, and low levels of digital literacy among users. The proposed optimization strategies include enhancing system interoperability, providing intensive training for court staff, and strengthening technical regulations to ensure consistent implementation. This study contributes theoretically to the discourse on e-Government-based public service innovation and offers practical recommendations for the Supreme Court and district courts in building more responsive, transparent, and sustainable public services.